Quaternization of Vinyl/Alkynyl Pyridine Enables Ultrafast Cysteine‐Selective Protein Modification and Charge Modulation. (9th April 2019) - Matos, Maria J.; Navo, Claudio D.; Hakala, Tuuli; Ferhati, Xhenti; Guerreiro, Ana; Hartmann, David; Bernardim, Barbara; Saar, Kadi L.; Compañón, Ismael; Corzana, Francisco; Knowles, Tuomas P. J.; Jiménez‐Osés, Gonzalo; et al.
Abstract: Quaternized vinyl‐ and alkynyl‐pyridine reagents were shown to react in an ultrafast and selective manner with several cysteine‐tagged proteins at near‐stoichiometric quantities. We have demonstrated that this method can effectively create a homogenous antibody–drug conjugate that features a precise drug‐to‐antibody ratio of 2, which was stable in human plasma and retained its specificity towards Her2+ cells. Finally, the developed warhead introduces a +1 charge to the overall net charge of the protein, which enabled us to show that the electrophoretic mobility of the protein may be tuned through the simple attachment of a quaternized vinyl pyridinium reagent at the cysteine residues. We anticipate the generalized use of quaternized vinyl‐ and alkynyl‐pyridine reagents not only for bioconjugation, but also as warheads for covalent inhibition and as tools to profile cysteine reactivity. Abstract : Die Quaternisierung des Stickstoffs von Vinyl‐ und Alkinyl‐Pyridinreagenzien ermöglicht die selektive und ultraschnelle Modifikation von Cystein in nahezu stöchiometrischen Mengen. Stabile und definierte Antikörper‐Wirkstoff‐Konjugate lassen sich auf diese Weise herstellen. Außerdem kann die elektrophoretische Mobilität des Proteins moduliert werden, indem eine einfach positive Ladung in das System eingeführt wird, wie mittels Mikrofluidik gezeigt wurde.